Numerical Modeling of a Two-tower Type Fluidized Receiver for High Temperature Solar Concentration by a Beam-down Reflector System. (May 2015) - Matsubara, K.; Sakai, H.; Kazuma, Y.; Sakurai, A.; Kodama, T.; Gokon, N.; Cho, H.S.; Yoshida, K.
Abstract: This study describes the flow and thermal field ofatwo-tower fluidized receiver, aimed tobeincorporated into a beam-down reflector system.Anexperimental visualization and numerical simulation were made to accumulate phenomenological knowledge, in order to complete the design of ademonstration model.Visualization of the cold particle bed with no irradiation revealed that global circulation occurs between the two towers by the aeration with different line velocities.The numerical simulation revealed that this global circulation enhancesthe transport of sensible heat from the irradiated layer in the high pressure tower to the low pressure tower.The global circulation in the two-tower fluidized receiver has the potential to be extended foruse inathermal receiver and direct storage system.Unexpectedly, local circulations occur on the high and low pressure sides, and are stronger than the global circulation.These local circulations contribute tothe thermal mixing in each tower.The bottom distributor onthe low pressure side can cause an uprising flowwhichleadsto the local circulation.The design of the distributor is suggested to be elaborated based on these findings.